Role of Body Dysmorphic Disorder in Patients With Postparalytic Facial Synkinesis. (17th March 2021) - Volk, Gerd Fabian; Hesse, Susanne; Geißler, Katharina; Kuttenreich, Anna‐Maria; Thielker, Jovanna; Dobel, Christian; Guntinas‐Lichius, Orlando
Abstract : Objectives/Hypothesis: To evaluate the role of body dysmorphic disorder (BDD) in patients with postparalytic facial nerve syndrome with synkinesis (PFS). Study Design: A single‐center retrospective cohort study. Methods: A total of 221 adults (74% women; median age: 44 years; median duration since onset of facial palsy: 1.6 years) were included. To diagnose BDD, the BDD Munich Module was used. Associations with House‐Brackmann grading, Stennert index grading, Facial Clinimetric Evaluation (FaCE) survey, Facial Disability Index (FDI), general quality of life (SF‐36), Beck Depression Inventory (BDI), and the Liebowitz Social Anxiety Scale (LSAS) was analyzed. Results: A total of 59 patients (27%) were classified as patients with BDD. Significant associations were found between the diagnosis of BDD and female gender and lower FDI, FaCE, and SF‐36 scores and higher BDI and LSAS scores. Multivariate analysis revealed BDI, FaCE total score, and FaCE social function subscore as independent factors associated with BDD. Conclusion: BDD was a relevant diagnosis in patients with PFS. A higher BDD level was associated with general and facial‐specific quality of life and more psychosocial disabilities. Optimal treatment of PFS has to include these nonmotor dysfunctions. Level of Evidence: 3 Laryngoscope, 131:E2518–E2524, 2021